(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article it will be exposed information about pragmatic competence as a structural component of foreign language communicative competence during teaching process. Pragmatic competence, the ability to use language appropriately in various social and cultural contexts, is increasingly recognized as an essential component of foreign language communicative competence. Despite its importance, pragmatic competence has often been neglected in traditional language teaching, which primarily focuses on linguistic forms like grammar and vocabulary. This article explores the role of pragmatic competence in foreign language learning and highlights its importance for effective communication. It further examines how pragmatic competence can be developed through teaching strategies, the challenges faced by both learners and instructors, and the potential methods for integrating pragmatic competence into language curricula. This article concludes by proposing ways to address the gap between linguistic competence and pragmatic skills, thereby improving foreign language education.